Comparative outcomes of invasive versus conservative strategy in stable coronary artery disease patients: a risk-stratification-based hypothesis-generative study - Zizhao Qi; Miaohan Qiu; Ying Xu; Kai Xu; Haiwei Liu; Xiaozeng Wang; Jing Li; Bin Liu; Shaoliang Chen; Jiyan Chen; Yaling Han; Yi Li (BMC Medicine)
Abstract Background Whether percutaneous coronary intervention (PCI) can improve the long-term prognosis of patients with stable coronary artery disease (SCAD) in comparison to conservative treatment remains controversial. The present study sought to evaluate the impacts of initial invasive versus conservative strategy on long-term clinical outcomes for patients with SCAD stratified by risk scores. Methods This was a sub-analysis of the multicenter, observational Optimal antiPlatelet Therapy for Chinese patients with Coronary Artery Disease (OPT-CAD) study. Clinical outcomes were compared in SCAD patients who initially received PCI (invasive strategy) or conservative treatment according to risk stratification by OPT-CAD score. The primary outcome was ischemic events at 5 years, composed of cardiac death, myocardial infarction, and ischemic stroke. Secondary outcomes included all-cause death, Bleeding Academic Research Consortium (BARC) types 2, 3, or 5, and 3 or 5 bleeding. Results The conservative group comprised 1767 (58.0%) patients and the invasive group comprised 1278 (42.0%) patients. Overall, invasive strategy did not reduce the risk of ischemic events compared with conservative strategy but was associated with an increased risk of BARC 2, 3, or 5 bleeding (adjusted hazard ratio (HR), 1.59; 95% confidence interval (CI), 1.13–2.26; P = 0.009). Similar results were observed in the low-risk patient subset (N = 2030). While in the moderate-to-high-risk subset (N = 1015), invasive strategy was associated with a reduced risk of ischemic events (HR, 0.67; 95% CI, 0.48–0.95; P = 0.02) and all-cause death (HR, 0.73; 95% CI, 0.51–1.03; P = 0.07), and with no excessive risk of bleeding. Conclusions Invasive strategy could not confer additional clinical benefits in patients with SCAD compared to conservative strategy, except in patients at moderate-to-high risk. The OPT-CAD risk score may be valuable to the guidance of optimal treatment strategy in SCAD patients.